Artificial Intelligence-Based Mathematics Learning Training for Vocational High School Students - Kadarisma, Gida; Minarti, Eva Dwi; Hutajulu, Masta; Sarinignsih, Ratna (Fakultas Keguruan dan Ilmu Pendidikan-Universitas Timor, 2025)
The rapid development of Artificial Intelligence (AI) technology has brought significant changes to the field of education, particularly in the teaching and learning of mathematics. The growing demand for AI integration in education calls for immediate action to equip both students and teachers with the necessary understanding and skills. However, initial analysis indicates that the majority of students and teachers at the partner school still lack a clear understanding of how to effectively utilize AI in the learning process. This community service activity aimed to enhance the understanding of vocational high school (SMK) students in utilizing AI technology to support more interactive and effective mathematics learning. The program was conducted in the form of a training session at SMKN 1 Cihampelas, involving 80 students. The implementation methods included the delivery of basic AI concepts, demonstrations of AI-based applications (such as ChatGPT, Photomath, and MathSolver), as well as hands-on practice and discussion sessions. Evaluation results showed that students responded positively, with 77% demonstrating an understanding of AI application in mathematics learning. This activity is expected to serve as an initial step toward the sustainable integration of AI technology in the vocational school environment